Die sterwende kindjie - J.T. De Jongh van Arkel (AOSIS, 1983)
The thought of a child dying appears as an antithesis and thus the feelings evoked by the dying child are stronger than when older persons are dying. Around the child's death bed there is no place for detached spectators and all become involved in caring for and supporting him. Caregivers also have a supporting responsibility towards the members of the child's family.